Public Debt and the Pasinetti Paradox - Vincenzo Denicolò; Massimo Matteuzzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
The main purpose of this paper is to show that the Cambridge Theorem holds independently of Ricardian Equivalence, if the net rate of profits is properly defined.
Keywords: 330